Study on Eating Habits and Physical Activity Status in Turkey - Bagriacik, Nazif; Elmacioglu, Funda; Sakar, Sule; Yolacan, Ceren; Yildiz, Sema (Journal of Nutritional Therapeutics, 2013)
The present study aimed to evaluate eating habits and physical activity status of Turkish population, and to determine nutritional changes. This study was conducted in 12 provinces of 11 regions of NUTS level 1 via a face-to-face interview using a pre-prepared questionnaire and included 1536 subjects aged >15 years with different socioeconomic statuses who eat out at least once in a month. Of the subjects, 33.6% were overweight, 18.4% were obese and 48% had normal weight. BMI % Overweight 33.6% Obese 18.4% Normal Weight 48.0% The rates of subjects calculating calorie intake (8.4%) and reading nutrition facts label (29.1%) were increased with increasing BMI. The most frequently consumed foods were bread, cheese and olive at breakfast, bread, soup, salad, yoghurt, and pilaf at lunch and toast, sandwiches, and Turkish bagels at snacks. Breakfast Average(Monthly) Bread 25.8 Cheese 25.0 Olive 22.8 Lunch Average(Monthly) Bread 26.1 Salad 17.7 Soup 16.4 Yoghurt 10.4 Pilaf 9.6 Snack % Toast 33.4 Turkish Bagels 26.3 Sandwiches 25.8 The mean duration of meals was <30 min in 85.8% of the subjects. Duration Of Meals % 0-15 minutes 22.7 16-30 minutes 63.3 30 minutes and more 14.1 The most commonly consumed non-alcoholic beverages were tea (95.7%), coffee (58.7%), Turkish yoghurt drink (56.1%), and carbonated beverages (48.3%). Milk consumption was low (20.2%). Non-alcoholic Beverages % Tea 95.7% Coffee 58.7% Turkish Yoghurt Drink 56.1% Carbonated Beverages 48.3% Milk 20.2% Alcohol consumption rate was 26.6%. The rate of subjects doing sports was 14.8%, which decreased with increasing age and BMI. In Turkish population, eating habits continued to be traditional, eating awareness and the rate of sport activities were very low.